The 360 leader developing your influence from anywhere in the organization - Maxwell, John C. (Nashville Nelson Business, 2005)
What?s the number one question leadership expert John C. Maxwell is asked while conducting his leadership conferences? ?How can I implement what you teach when I?m not the top leader??. Is it possible to lead well when you?re not the top dog? How about if the person you work for is a bad leader? The answer is a resounding yes!
Keywords: Leadership